Macroeconomic Determinants of Renewable Energy Production in Jordan - Alkhawaldeh, Bashar Younis; Al-Smadi, Arkan Walid; Ahmad, Ahmad Y. A. Bani; El-Dalahmeh, Suleiman Mustafa; Alsuwais, Najwa; Almarshad, Mohammad Nassar (International Journal of Energy Economics and Policy, 2024)
Using the years 1970–2022, this research looks at the macroeconomic variables that have an impact on Jordan's renewable energy production. To assess the main factors impacting Jordan's renewable energy scenario, the study employed the Dynamic Autoregressive Distributed Lag (DARDL) tool. Several important aspects affecting renewable energy production are highlighted in the study. A multitude of factors that statistically and positively impact the attainment of renewable energy are diverse economic activities as measured by the GDP. The contribution of a fair economy in speeding up and maintaining promotion of renewable energy projects in Jordan is noticeable. Moreover, FDI is one of the factors in fostering renewable energy production and its role is very significant and positive, thus, it is affecting renewable energy production in a great extent. In a nutshell, overseas funding should be meant to yield a great harvest in planting and constructing Jordanian renewable energy plants and equipments. The study also indicates that finance is not just fundamental for renewable energy movement but for the evolution of the renewable energy industry as well. While the tried and true fact of the positively and statistically significant case of link between renewable energy production and financial development underline the vital role of a financially prosperous area in redirecting investments from traditional resources to renewable energy and therefore contribute to its further expansion. However, that idea needed some modification due to the disagreement that the CO2 emissions also have significant role in reducing renewable energy production. The study has identified that there is a negative correlation between the carbon emissions and renewable energy production if it is computed statistically. The implementation of more effective policies and initiatives that will result in reduced carbon emissions becomes possible with all sectors working together to form a better environment for the establishment of renewable energy infrastructures.